Artificial insect wings with biomimetic wing morphology and mechanical properties. (25th September 2017) - Liu, Zhiwei; Yan, Xiaojun; Qi, Mingjing; Zhu, Yangsheng; Huang, Dawei; Zhang, Xiaoyong; Lin, Liwei
Abstract: The pursuit of a high lift force for insect-scale flapping-wing micro aerial vehicles (FMAVs) requires that their artificial wings possess biomimetic wing features which are close to those of their natural counterpart. In this work, we present both fabrication and testing methods for artificial insect wings with biomimetic wing morphology and mechanical properties. The artificial cicada ( Hyalessa maculaticollis ) wing is fabricated through a high precision laser cutting technique and a bonding process of multilayer materials. Through controlling the shape of the wing venation, the fabrication method can achieve three-dimensional wing architecture, including cambers or corrugations. Besides the artificial cicada wing, the proposed fabrication method also shows a promising versatility for diverse wing types. Considering the artificial cicada wing's characteristics of small size and light weight, special mechanical testing systems are designed to investigate its mechanical properties. Flexural stiffness, maximum deformation rate and natural frequency are measured and compared with those of its natural counterpart. Test results reveal that the mechanical properties of the artificial cicada wing depend strongly on its vein thickness, which can be used to optimize an artificial cicada wing's mechanical properties in the future. As such, this work provides a new form of artificial insect wings which can be used in the field of insect-scale FMAVs.